Determinants of participation decisions and level of participation in farm level milk value addition: The case of smallholder dairy farmers in Ethiopia - Kuma, B.; Getnet, Kindie; Baker, Derek; Kassa, B. (2011)
On-farm value addition to farm products is recognized and highly promoted through value chain approaches for its benefit in terms of improving farm income. Growing demand and high price for value added milk products, together with the availability of ample livestock resources, would provide opportunities for smallholder farmers in Ethiopia to diversify their livelihoods. Nevertheless, their participation in milk value addition is perceived to be generally low. Apart from farm household characteristics, organizational and institutional issues influence farmers’ participation decisions and level of participation in-farm level milk value addition. By analyzing survey data using Heckman two-stage selection model, this article identified determinants of participation decisions and level of participation in-farm level milk value addition by smallholder farmers in Ethiopia. The first-stage probit model estimation results indicate that milk yield, distance from urban centers, household demography (age and child), livestock extension services, the need to extend shelf life, consideration of milk products for social factors such as holidays and fasting, and availability of labor for milk value addition determined household’s decision to add values to milk. The results also show that most of the factors determining decision of participation in milk value addition also determined the level of participation.